The Changing Demographics of Women Living with HIV/AIDS in Southern Alberta from 1982 to 2006. Issue 2 (2012) - Hwang, Liana; Raffa, Jesse; Gill, Michael John
Abstract : INTRODUCTION: Women account for a growing proportion of HIV infections in Canada. This has implications with respect to prevention, diagnosis and treatment. OBJECTIVE: To describe the female population presenting for HIV care in southern Alberta and to examine the impact of opt-out pregnancy screening. METHODS: A retrospective review of demographic and clinical characteristics of all patients presenting to the Southern Alberta HIV Clinic (SAC) care program from 1982 to 2006, was performed. RESULTS: The proportion of newly diagnosed patients who were female increased from 7.5% before 1998 to 21.5% after 1998. Women were more likely to be from vulnerable populations, such as intravenous drug users (31.3% versus 13.7%, P<0.001), aboriginals/Métis (21.5% versus 8.7%, P<0.001), blacks (28.9% versus 4.9%, P<0.001) and immigrants (36.6% versus 14.7%, P<0.001). Heterosexual intercourse was the main risk factor for HIV acquisition (43.7%). Women were less likely than men to have requested HIV testing (20.9% versus 37.8%, P<0.001). Opt-out pregnancy screening accounted for 12.7% of HIV-positive tests in women, following its introduction in 1998. Of the women diagnosed by pregnancy screening, 62.1% were from HIV-endemic countries. There was an association between reason for testing and CD4 count at presentation; women who requested their HIV test had higher median CD4 counts than those diagnosed because of illness (478 cells/mL, interquartile range [IQR]=370 cells/mL versus 174 cells/mL, IQR=328 cells/mL, P<0.001) or pregnancy screening (478 cells/mL, IQR=370 cells/mL versus 271 cells/mL, IQR=256 cells/mL, P=0.001). CONCLUSIONS: Women were less likely than men to have requested HIV testing and were more likely to be diagnosed by population-based screening methods. Women, especially vulnerable groups, account for a growing number and proportion of newly diagnosed HIV infections in Alberta. The implications of expanded screening in this population merit further consideration.